Cerebral Large Vessel Occlusion Caused by Fat Embolism—A Case Series and Review of the Literature - Ooi, Suyi; Raviskanthan, Subahari; Campbell, Bruce C. V.; Hutton, Elspeth J.; Mitchell, Peter J.; Cloud, Geoffrey C. (Frontiers in Neurology, 2021)
The diagnosis of fat embolism syndrome typically involves neurological, respiratory and dermatological manifestations of microvascular occlusion 24 – 72 hours after a precipitating event. However, fat embolism causing cerebral large vessel occlusion strokes and their sequelae have rarely been reported in the literature. This case series reports three patients with fat emboli post operatively causing cerebral large vessel occlusions, as well as a review of the literature to identify differences in clinical presentations and outcomes in stroke secondary to fat emboli causing large vessel occlusions compared to those with fat embolism syndrome.